Sudden cardiac death in football - Bohm, P.; Kästner, A.; Meyer, T. (Journal of Sports Sciences, 2013)
Football is the most popular sport worldwide and includes the largest population of sports participants, especially in the field of recreational sport. It remains controversial whether football represents a sport discipline with a particular high risk of sudden cardiac death (SCD). The true incidence of SCD among football players is not known due to a lack of football-specific studies. In particular, recreational football players over an age of 35 years with a predominance of coronary artery disease (CAD) who do not exercise regularly are exposed to a higher risk of SCD. Surprisingly, the few European studies that included football as a sport discipline, showed that CAD already plays an important role in the young athlete. Potential pathophysiological mechanisms in football that may lead to a higher risk of SCD include the high release of catecholamines, increased platelet aggregation, dehydration and electrolyte disturbances. Establishment of sport-specific and national registers for SCD should certainly contribute to a better understanding of this highly important topic.